ZIF-12/Fe-Cu LDH Composite as a High Performance Electrocatalyst for Water Oxidation - Hameed, Arslan; Batool, Mariam; Iqbal, Waheed; Abbas, Saghir; Imran, Muhammad; Khan, Inayat Ali; Nadeem, Muhammad Arif (Frontiers in Chemistry, 2021)
Layered double hydroxides (LDH) are being used as electrocatalysts for oxygen evolution reactions (OERs). However, low current densities limit their practical applications. Herein, we report a facile and economic synthesis of an iron-copper based LDH integrated with a cobalt-based metal-organic framework (ZIF-12) to form LDH-ZIF-12 composite (1) through a co-precipitation method. The as-synthesized composite 1 requires a low overpotential of 337 mV to achieve a catalytic current density of 10 mA cm−2 with a Tafel slope of 89 mV dec−1. Tafel analysis further demonstrates that 1 exhibits a slope of 89 mV dec−1 which is much lower than the slope of 284 mV dec−1 for LDH and 172 mV dec−1 for ZIF-12. The slope value of 1 is also lower than previously reported electrocatalysts, including Ni-Co LDH (113 mV dec−1) and Zn-Co LDH nanosheets (101 mV dec−1), under similar conditions. Controlled potential electrolysis and stability test experiments show the potential application of 1 as a heterogeneous electrocatalyst for water oxidation.